Low Myostatin Serum Levels Are Associated with Poor Outcome in Critically Ill Patients - Wirtz, Theresa H. (Diagnostics (Basel), 2020)
Background: Growth differentiation factor 8, GDF-8 (Myostatin), is a protein released by myocytes inhibiting muscle growth and differentiation. Serum concentrations of Myostatin can predict poor survival in different chronic diseases, but its role in critical illness and sepsis is obscure. Our aim was to investigate Myostatin levels as a potential prognostic biomarker in critically ill patients with sepsis. Methods: We therefore measured Myostatin serum concentrations in 165 critically ill patients (106 with sepsis, 59 without sepsis) upon admission to the medical intensive care unit (ICU), in comparison to 14 healthy controls. Results: Myostatin levels were significantly decreased in ICU patients compared to controls but did not differ in patients with or without sepsis. However, Myostatin concentrations were significantly lower in patients requiring mechanical ventilation and indicated a trend towards dependency of intravenous vasopressors. Interestingly, we observed a negative correlation between Myostatin levels and markers of systemic inflammation. Strikingly, overall survival (OS) was significantly impaired in patients with low Myostatin levels in all critically ill patients. Low Myostatin levels at baseline turned out as an independent prognostic marker for OS in multivariate Cox-regression analysis (HR: 0.433, 95% CI: 0.211–0.889, p = 0.023). Conclusions: In summary, serum Myostatin concentrations are significantly decreased in critically ill patients and associated with disease severity. Low Myostatin levels also identify a subgroup of ICU patients that are more likely to face an unfavorable clinical outcome in terms of OS.